2016
DOI: 10.1016/j.ebiom.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Immunoglobulin G and M Levels Predict Freedom From Adverse Cardiovascular Events in Hypertension: A Nested Case-Control Substudy of the Anglo-Scandinavian Cardiac Outcomes Trial

Abstract: AimsWe aimed to determine whether the levels of total serum IgM and IgG, together with specific antibodies against malondialdehyde-conjugated low-density lipoprotein (MDA-LDL), can improve cardiovascular risk discrimination.Methods and ResultsThe Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) randomized 9098 patients in the UK and Ireland into the Blood Pressure-Lowering Arm. 485 patients that had cardiovascular (CV) events over 5.5 years were age and sex matched with 1367 controls. Higher baseline total se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 38 publications
2
46
2
Order By: Relevance
“…In contrast to their role in mouse studies,28, 33 CD43 + B cells, suggested to resemble B1 cells in mice,15 did not associate with protection against secondary events in our study. Contrasting results have been reported for the association of serum IgM levels with primary cardiovascular events 51, 52, 53. In our study, patients with high numbers of unswitched memory cells expressed more IgM on their cell surface, suggesting an increased production and release of IgM antibodies.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to their role in mouse studies,28, 33 CD43 + B cells, suggested to resemble B1 cells in mice,15 did not associate with protection against secondary events in our study. Contrasting results have been reported for the association of serum IgM levels with primary cardiovascular events 51, 52, 53. In our study, patients with high numbers of unswitched memory cells expressed more IgM on their cell surface, suggesting an increased production and release of IgM antibodies.…”
Section: Discussioncontrasting
confidence: 99%
“…High levels of IgM-type antibodies to MDA and phosphorylcholine reduce the risk for cardiovascular disease, [5][6][7] although not in all studies. 8,9 In contrast, IgG antibodies of similar specificity can in some cases be positively associated with disease 10 but more commonly show no association. 5,8,9 Recently, total serum IgG and IgM, in addition to oxLDL-specific, was associated with reduced risk of cardiovascular events.…”
Section: Meet the First Author See P 198mentioning
confidence: 97%
“…8,9 In contrast, IgG antibodies of similar specificity can in some cases be positively associated with disease 10 but more commonly show no association. 5,8,9 Recently, total serum IgG and IgM, in addition to oxLDL-specific, was associated with reduced risk of cardiovascular events. 9 In mice, many studies suggest IgM antibodies provide an important atheroprotective layer.…”
Section: Meet the First Author See P 198mentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, both total IgM and MDA-LDL-specific IgM are inversely associated with cardiovascular disease complications in individuals of the AngloScandinavian Cardiac Outcomes Trial. 29 Interestingly, recent work indicates that IgE promote lupus like autoimmunity in mice 30 and that the presence of autoreactive IgE positively associates with disease activity in systemic lupus erythematosus (SLE) patients. 31 Notably, lupus-prone mice lacking sIgM develop enhanced autoimmune pathology compared with their controls.…”
Section: A] Newman-keuls [B] Unpaired T Test and [C-e] Unpaired T Tmentioning
confidence: 99%